A Comparative Analysis of Islamic Religious Education in Senior, Vocational, and Islamic High Schools under the Merdeka Curriculum - Falah, Riza Zahriyal; Qomariyah, Siti; Nazaruddin, Muhamad Sophian (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
This study examines the implementation of the Merdeka Curriculum in Islamic Religious Education at three types of secondary schools in Kudus: senior, vocational, and Islamic high schools. The study addresses challenges such as the gap in teachers' ability to integrate technology, limited learning time, and the need for content adaptation. Using a qualitative approach, data were collected through in-depth interviews with 12 Islamic religious education teachers and direct observation at senior, vocational, and Islamic high schools. The research findings reveal significant variations in the implementation of the curriculum. The vocational high school excels in integrating the EMIRA digital platform and developing co-curricular projects relevant to the world of work. Senior high schools excel in developing a holistic evaluation system, although they face challenges in increasing student engagement. Meanwhile, Islamic high schools are still in the early stages of adaptation, primarily focusing on preparing appropriate curriculum documents. This study demonstrates that the Merdeka Curriculum has the potential to enhance the relevance of Islamic religious education learning to students' real-life experiences. However, its implementation still faces various technical and pedagogical challenges. These findings provide important implications for the development of educational policies and teacher training programs in the future.